Rivalry : - Brenner, Reuven (The Cambridge University Press, 1987)
Rivalry is an attempt to understand facets of entrepreneurial societies by integrating the economic analysis with historical, political and psychological considerations, customarily shunned by economists. The author argues that decisions to make new business ventures, and readiness to take risks are both related to concepts of ranking hierarchies on local, national or international levels. He then constructs a theory of business enterprise and of rivalry supported by evidence on entrepreneurship, innovation, advertising, all examined with their historical, political or organisational concerns